A Qualitative Evaluation of the Pain Management VA-ECHO Program Using the RE-AIM Framework: The Participant's Perspective - Ball, Sherry; Stryczek, Krysttel; Stevenson, Lauren; Hearns, Rene; Au, David H.; Ho, P. Michael; Aron, David C. (Frontiers in Public Health, 2020)
Veterans frequently seek chronic pain care from their primary care providers (PCPs) who may not be adequately trained to provide pain management. To address this issue the Veterans Health Administration (VHA) Office of Specialty Care adopted the Specialty Care Access Network Extension for Community Healthcare Outcomes (VA-ECHO née SCAN-ECHO). The VA-ECHO program offered training and mentoring by specialists to PCPs and their staff. VA-ECHO included virtual sessions where expertise was shared in two formats: 1) didactics on common pain conditions, relevant psychological disorders, and treatment options and 2) real-time consultation on patient cases. VA-ECHO participants’ perspectives were obtained using a semi-structured interview guide designed to elicit responses based on the RE-AIM (reach, effectiveness, adoption, implementation, and maintenance) framework. A convenience sampling was used to recruit PCPs and non-physician support staff participants. Non-physicians from rural VHA sites were purposively sampled to gain diverse perspectives. This qualitative study yielded data on each RE-AIM domain except reach. Program reach was not measured as it is outside the scope of this study. Respondents reported program effectiveness as gains in knowledge and skills to improve pain care delivery. Effective incorporation of learning into practice was reflected in respondents’ perceptions of improvements in: patient engagement, evidenced-based approaches, appropriate referrals, and opioid use. Program adoption included how participating health care systems selected trainees from a range of sites and roles to achieve a wide reach of pain expertise. Participation was limited by time to attend and facilitated by institutional support. Differences and similarities were noted in implementation between hub sites. Maintenance was revealed when respondents noted the importance of the lasting relationships formed between fellow participants. This study highlights VA-ECHO program attributes and unintended consequences. These findings are expected to inform future use of VA-ECHO as a means to establish a supportive consultation network between primary and specialty care providers to promote the delivery evidence-based pain management practices.